EEG Based Emotion Recognition Approches and Challenges: a Review - K S, Bhanumathi; D, Jayadevappa (International Journal of Psychosocial Rehabilitation, 2020)
Emotion plays a very important role in day to day life of human beings because of its direct influence on brain that governs desicison making, perception, memory and behavioral aspects. Many researchers have established that, emotion is a complex set of interactions among subjective and objective factors regulated by neural/hormonal systems which activate physiological changes. Since the Electroencephalography (EEG) ensures a stronger reliability in the psychological signals, it receives significant attention for identifying emotions. Therefore providing a comprehensive overview of the existing works in emotion recognition using EEG signals is necessary. This paper provides brief analysis of various classifiers used in emotion recognition process and their challenges in emotion recognition systems.